Acute kidney injury in pediatric hematopoietic stem cell transplant recipients - Fitzgerald, Julie C. (J Pediatr Intensive Care, 2014)
Acute kidney injury is common after pediatric hematopoietic stem cell transplant with a reported incidence of 21–55% in the first 3 mo after transplant. Acute kidney injury is associated with decreased survival and the development of chronic kidney disease in this patient population. In this review, current definitions of acute kidney injury are discussed. The epidemiology and risk factors for acute kidney injury in this patient population are described, and current hypotheses on the pathophysiology are reviewed. Current and emerging ideas about changes to management strategies to mitigate acute kidney injury are presented, and areas for further research are proposed.